Agripreneurship insights and lessons from Zadeva Investments (Namibia) - Shitaatala, Eva (Technical Centre for Agricultural and Rural Cooperation, 2018)
Eva Shitaatala, Director of Zadeva investments (Namibia) shares her entrepreneurial journey and insights on how some of the challenges that she is facing can be overcome.